Numerical Analysis of a Pile-Soil System Under Earthquake Loading - Shafiqu, Qassun S. Mohammed; Sa'ur, Ruba H. Majeed (Al-Nahrain Journal for Engineering Sciences, 2017)
Due to significant increasing in seismic activity in world during the last decades especially in Middle East region; engineers have been giving increasing attention to the design of buildings for earthquake resistance. In this study 3-D seismic behavior of piles is investigated using the finite element program PLAXIS 3D 2013. _x000D_Piles are one of the most commonly used foundations in seismic areas where the soil is inadequate to carry the load on its own. In these seismic areas, piles often pass through (penetrate) shallow loose and/or soft soil deposits and rests on competent end bearing soils. Thus a model of soil - pile system is simulated in the finite element program._x000D_The dynamic parameters of soil are used as input dynamic data of PLAXIS 3D program, in addition to the static properties of soil collected from soil investigation works._x000D_The research showed the susceptibility of PLAXIS 3D program in analyzing piles with different soil conditions under earthquake action. The results also showed the importance of studying seismic behavior of soil-pile system using 3-D analysis rather than 2-D analysis because the problem is truly 3-D and should be analyzed as such.